Creep Behavior and Its Prediction of Saturated Weakly Cemented Medium-Grained Sandstone under Multiaxial Loadings. (6th February 2023) - Gu, Qingheng; Zhao, Guangming; Meng, Xiangrui; Sun, Jian; Cheng, Xiang; Xu, Wensong; Zhang, Ruofei
Abstract : Weakly cemented medium-grained sandstone in Ordos mining area of China is widely distributed under phreatic water. The creep behavior of saturated rock is important for the stability of water-resisting strata. In this paper, creep mechanical properties of saturated medium-grained sandstone were studied by triaxial rheological test. The results showed that medium-grained sandstone only shows attenuation creep and stable creep under low stress level, and accelerated creep occurs when axial load reaches about 75% of instantaneous compressive strength. The rock samples exhibit volume dilatancy under most loading levels and finally shear fracture. The failure mechanism is the dislocation separation of mineral particles. Based on the energy dissipation theory, the damage evolution equation was modified and introduced into the Burgers model, which can accurately describe the rheological behavior of saturated medium-grained sandstone. The modified model was used to predict the crack initiation time under different deviatoric stresses, which can provide guidance for early warning of water-resisting rock stability.